Unele repere cu privire la munca forţată (reglementări naționale și internaţionale) [Articol] - Romandaș, Nicolae (Tipografia Print-Caro, 2021)
In this article, a comprehensive analysis of the subject of forced labor through national and international legislation was made. In particular, reference was made to the ILO Conventions, the European Convention on Human Rights, etc. An interpretation of the concept of forced labor has been made, which combines several elements and, as a result, the difference between the notion of compulsory labor and that of forced labor has been established to prove the existence of forced labor. Also, the reasons for the imposition of forced labor and the cases attributed by the labor legislation to the concept of forced labor, including the work of minors were commented on.
SOME GUIDELINES ON FORCED LABOR (NATIONAL AND INTERNATIONAL REGULATIONS)
Keywords: ILO Convention; forced labor; working conditions; sanctioning procedure; disciplinary violations; coercive methods